TECHNICAL EFFICIENCY OF COFFEE FARMING IN LIMA PULUH KOTA REGENCY, WEST SUMATRA PROVINCE - Andini Puspa Yoga; Rahmat Syahni; Hasnah Hasnah (Jurnal Ekonomi, 2023)
Technical efficiency is the ability to avoid waste by producing as much output as possible with existing inputs and technology or by using fewer inputs with the same technology that will produce the same output. Fifty Cities District is one of the areas that has potential in developing Robusta coffee plants. The available production factors cannot guarantee high productivity. The purpose of this study was to analyze the factors that influence the productivity of Robusta coffee, analyze the level of technical efficiency of Robusta coffee farming and analyze the factors that affect the technical efficiency of Robusta coffee farming in the District of Fifty Cities. The method used in this study was a survey method on 60 samples through simple random sampling. Data analysis uses the Cobb-Douglas production function. The results showed that the factors that significantly influence coffee productivity in Fifty Kota District are the age of the plants and the number of trees. Factors of plant age and number of trees have a positive impact on coffee productivity. The technical efficiency level of coffee farming in Lima Puluh Kota Regency ranges from 0.54 to 0.99 with an average technical efficiency level of 0.83. This means that farmers are technically efficient but can still increase coffee productivity.